PELATIHAN MANAJEMEN KEBERSIHAN MENSTRUASI PADA GURU SD DAN SMP - Umniyati, Helwiah (Divisi Pengabdian dan Pemberdayaan Masyarakat (DP2M) UNIKOM, 2025)
ABSTRACT School Sanitation is an important element in improving the quality of education because it has a significant impact on improving the health and comfort of students at school, one of the components is Menstrual Hygiene Management (MKM). MHM is the management of hygiene and health when girls are menstruating. In Indonesia, MHM has been included in the UKS but has not received integrated attention and treatment and limited knowledge of teachers about MHM. Another important issue related to MHM is the fact that male students tend to bully female students who are menstruating. Because of the importance of MHM to school teachers, YARSI University in collaboration with UNICEF Indonesia conducted MHM training for teachers through a webinar enrolled by 385 teachers from many provinces in Indonesia, however only 121 teachers could be evaluated heir knowledges. Most of the MHM training participants (86.9%) were female teachers. After the training, there was a significant increase in the level of teacher knowledge about MHM by 55.6%, using the wilcoxom test showed that there was a significant difference between knowledge before and after education (p<0.05). Through training, it is hoped that the MHM program could be implemented in schools. Teachers can deliver MHM material as part of reproductive health lessons at school, implement MHM as a mandatory activity at UKS, and provide various facilities needed by students. Other important goal was that male students have a positive attitude towards female students so gender equality will be achieved. Key words: menstrual hygiene management; school; teacher ABSTRAK Manajemen Kebersihan Menstruasi (MKM) merupakan pengelolaan kebersihan dan kesehatan pada saat anak perempuan mengalami menstruasi. Di Indonesia, saat ini, MKM sudah masuk dalam UKS akan tetapi belum mendapat perhatian dan penanganan yang terintegrasi. Pentingnya isue MKM di sekolah terkait tiga hal yaitu rendahnya sarana sanitasi yang layak di sekolah, kurangnya akses informasi siswa mengenai pengelolaan kebersihan menstruasi secara baik dan benar, dan banyak guru yang belum tahu mengenai MKM. Tujuan dari PkM adalah melakukan sosialisasi MKM pada guru sekolah, Universitas YARSI bekerja sama dengan UNICEF Indonesia melakukan Pelatihan MKM pada guru sekolah melalui webinar yang diikuti oleh guru dengan peserta sebanyak 385 guru, akan tetapi hanya 121 peserta yang dapat dianalisis. Sebagian besar peserta pelatihan MKM (86,9%) adalah guru perempuan. Setelah pelatihan, terjadi peningkatan bermakna dari tingkat pengetahuan guru mengenai MKM sebesar 55,6%, dengan menggunakan uji wilcoxom memperlihatkan bawa terdapat perbedaan antara pengetahuan sebelum dan sesudah edukasi (p<0,05). Melalui pelatihan guru diharapkan program MKM dapat diterapkan di sekolah. Guru dapat menyampaikan materi MKM sebagai bagian dalam pelajaran kesehatan reproduksi di sekolah, melaksanakan MKM sebagai salah satu kegiatan wajib pada UKS, dan menyediakan berbagai fasilitas yang dibutuhkan siswa. Tujuan penting lainnya Siswa laki-laki dapat bersikap positif terhadap siswa perempuan dalam memenuhi kesetaraan gender. Kata kunci: manajemen kebersihan menstruasi; sekolah; guru